Hizbut Tahrir Indonesia and Its Implications on Social Religious Realm - Mujahiduddin Mujahiduddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
This article describes HizbututTahrir as a social movement in post-Suharto era, and his views on the re-establishment of the Islamic caliphate. In the perspective of the emergence of social movements can be said Hizbuu Tahrir Indonesia is clearly a response to a variety of damage that occurred in Indonesia ranging from poverty, injustice, corruption, and demoralization. Social disasters caused by the implementation of the Indonesian government or secular infidels (unbelievers) system emanating from Western values​​. To escape from such problems, HizbutTahrir and HTI is to encourage full implementation of Islamic Sharia from the restoration of the Islamic caliphate throughout the world. HTI is fully aware that to establish an Islamic caliphate requires collective action and support of many people.